2006
DOI: 10.1111/j.1600-0609.2006.00716.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient donor cell‐derived myelodysplastic syndrome with monosomy 7 after unrelated cord blood transplantation

Abstract: Donor cell leukaemia or myelodysplastic syndromes are extremely rare complications that have been observed not only after haematopoietic transplantation with progenitor cells harvested from bone marrow and peripheral blood, but also after cord blood transplantation. We describe the early onset of monosomy 7 in donor cells after cord blood transplantation in a patient diagnosed with myelodysplastic syndrome 3 months after transplantation. Fluorescent in situ hybridisation analysis performed in a cryopreserved a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…However, engraftment was transient in some cases, clonal markers indicated that 15-99% of the cells were derived from normal hematopoietic cells, and there was no evidence that the mice developed peripheral blood cytopenias or other evidence of clinical MDS. Rare case reports of donor-derived MDS in BM transplant recipients have suggested that MDS may be transplantable (27), although in most of these reports, there was no convincing evidence that the donor had MDS.…”
Section: Discussionmentioning
confidence: 95%
“…However, engraftment was transient in some cases, clonal markers indicated that 15-99% of the cells were derived from normal hematopoietic cells, and there was no evidence that the mice developed peripheral blood cytopenias or other evidence of clinical MDS. Rare case reports of donor-derived MDS in BM transplant recipients have suggested that MDS may be transplantable (27), although in most of these reports, there was no convincing evidence that the donor had MDS.…”
Section: Discussionmentioning
confidence: 95%
“…Donor-derived hematologic neoplasms are now recognized as a potential complication of UCB HSCT. Donor-derived EBV 1 B-cell PTLD and ddMDS/ddAML has also been previously reported after UCB HSCT [12][13][14][15][16][17][18][19][20]. Kaplan-Meier analysis of pooled data on 13 cases of ddAML after UCB HSCT seems to show an increased risk of ddAML, when compared with other sources of stem cells [21].…”
Section: Lettersmentioning
confidence: 78%
“…There are only six case reports highlighting that leukemic transformation may originate from donor cells after BMT for SAA [3,[10][11][12][13][14]. Rarely, this transformation also been reported after unrelated umbilical cord blood [15,16].…”
Section: Discussionmentioning
confidence: 99%